2013
DOI: 10.1007/s00198-013-2288-7
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid enhances bone-implant osseointegration more than alendronate and strontium ranelate in ovariectomized rats

Abstract: In rats losing bone rapidly after ovariectomy, systemic administration of ZOL, ALN, and SR causes better bone-implant osseointegration when compared to OVX; ALN and SR have similar positive effects on osseointegration, while ZOL, that was given in a dose with more positive BMD effect than that of ALN or SR, causes better osseointegration than either ALN or SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…The influence of the use of bisphosphonates in implant dentistry has been studied extensively, both their systemic use [27][28][29] and local use by means of direct application to the surgical alveolus 13,22,23,25 or by immobilization of the medication on the implant surface. 7,15,16,[19][20][21] In this study, local application of bisphosphonate was used in order to benefit from its biomodulating influence on osseointegration in the absence of the possible systemic effects of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the use of bisphosphonates in implant dentistry has been studied extensively, both their systemic use [27][28][29] and local use by means of direct application to the surgical alveolus 13,22,23,25 or by immobilization of the medication on the implant surface. 7,15,16,[19][20][21] In this study, local application of bisphosphonate was used in order to benefit from its biomodulating influence on osseointegration in the absence of the possible systemic effects of this drug.…”
Section: Discussionmentioning
confidence: 99%
“…Most osteoporotic animal models have utilized long bones, such as the tibia [15,17,18,45,46] or femur [16,47] and the results from these studies is of limited value in understanding the osseointegration of endosseous implants into the jaw in osteoporotic conditions. Compared with long bone, the jaw bone has a different embryological origin and a different ossification mechanism, as well as a different response to estrogen deficiency [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recent systematic review show that osteoporotic patients have higher rates of dental implant loss [13]. Many animal studies have reported a lower rate of titanium implant osseointegration in osteoporotic environments, however the majority of these studies used long bone [14][15][16][17][18] rather than jaw bone models [19]. As there are significant differences in the embryological origin, ossification process and the response to osteoporotic conditions between long bones and craniofacial bones [20,21], the relevance of results obtained in a long bone model to the oral environment is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…Alendronate (A) or [(4-amino-1-hydroxybutylidene)-bisphosphonate] trihydrate (see Scheme 1) is a nitrogencontaining stable representative of the bisphosphonates [1], which is able to interact with the bone matrix by inhibiting bone remodeling activity and resorption [2]. Studies have shown that sodium alendronate has strong bone-implant osteointegration and implant fixation properties [3] and is also used to treat osteoporosis and other osteolytic bone diseases [4].…”
Section: Introductionmentioning
confidence: 98%
“…However, taking into account the biological activity by the osteoblast-osteoclast equilibrium[2,4], we consider that the dehydration is not an event leading to the loss of the bioactive/therapeutic properties of the alendronate…”
mentioning
confidence: 99%